Performance and quality of eggs of laying hens fed with Moringa Oleifera leaf flour. - Rogério Ventura da Silva Junior; Carlos Bôa-Viagem Rabello; Maria do Carmo Mohaupt Marques Ludke; Cláudia da Costa Lopes; Waleska Rocha Leite de Medeiros Ventura; Elayne de Souza Rocha Soares; Patricia Maria Guedes Paiva; Thiago Henrique Napoleão; Apolonio Gomes Ribeiro; Júlio Cézar Dos Santos Nascimento; Lilian Francisco Arantes de Souza; Helia Sharlane de Holanda Oliveira (PLoS ONE)
The objective of this study was to evaluate the performance of commercial laying hens fed with different levels of Moringa oleifera leaf meal in their diet. For this purpose, 150 laying hens of the Dekalb White lineage, at 62 weeks of age, and with an initial average weight of 1.458 kg ± 8.70g, were used. They were housed in cages measuring 1.00 X 0.40 X 0.45m, equipped with chute-type feeders, automatic cup-type drinkers and chute for collecting eggs. They were distributed in a completely randomized design, consisting of five treatments with five replications of six birds. The treatments consisted of a reference diet, without moringa inclusion, and four test diets with levels of 1.5%, 3.0%, 4.5% and 6% inclusion of moringa leaf meal. Water was provided ad libitum, and 120 g of feed per bird per day. The total experimental period lasted 122 days. The data obtained were subjected to analysis of variance and Dunnett's test at 5% significance and, when significant, subjected to regression analysis. Analysis of the leaf flour revealed the presence of antinutritional factors in small concentrations. It was observed that the addition of moringa to the birds' diet did not influence performance parameters and provided significant increases in the average egg weight according to moringa inclusion levels of 1.5%, 4.5% and 6% when compared to the control diet, as well as a significant increase in the color of the egg yolks for all levels tested (1.5 to 6%). A reduction in Haugh unit values was observed when inclusion levels of moringa were 4.5% and 6%. Despite a reduction in Haugh unit values, they are still within the classification standards. Analysis of the biochemical parameters of the birds' blood serum did not show significant influences according to the levels of moringa inclusion in the diet, although a numerical reduction was observed in the cholesterol levels of birds fed with an inclusion of 6% of leaf flour in the diet, which could possibly be related to the presence of phytochemical compounds, more precisely β-sitosterol. Moringa oleifera leaf meal can be used to feed laying birds without causing harm to the birds' performance, in addition to intensifying the color of the yolks.